2016
DOI: 10.14341/dm7727
|View full text |Cite
|
Sign up to set email alerts
|

Incretin-based therapy: renal effects

Abstract: © Сахарный диабет, 2016ерапия, основанная на модификации эффекта инкретиновых гормонов, -сравнительно новое направление в лечении сахарного диабета 2 типа (СД2). Аналоги глюкагоноподобного пептида 1 типа (ГПП-1) и ингибиторы дипептидилпептидазы 4 типа (ДПП-4) обладают широким спектром фармакологиче-ского действия, включающего гликемические и неглике-мические эффекты. В последние годы большой интерес вызывает способность препаратов данных классов вли-ять на развитие осложнений СД. В настоящем обзоре обобщены ре… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0
3

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 93 publications
(103 reference statements)
0
10
0
3
Order By: Relevance
“…A growing body of evidence indicates that DPP4 inhibitors could produce multiple pleiotropic effects independent of lowering glucose levels[19,20]. In this study, we demonstrated the beneficial effects of the DPP4 inhibitor linagliptin on both parenchymal and non-parenchymal hepatic cells in T2D db/db mice (BKS.Cg- Dockm м +/+ Lepr db /J).…”
Section: Discussionmentioning
confidence: 53%
“…A growing body of evidence indicates that DPP4 inhibitors could produce multiple pleiotropic effects independent of lowering glucose levels[19,20]. In this study, we demonstrated the beneficial effects of the DPP4 inhibitor linagliptin on both parenchymal and non-parenchymal hepatic cells in T2D db/db mice (BKS.Cg- Dockm м +/+ Lepr db /J).…”
Section: Discussionmentioning
confidence: 53%
“…It is well known that both SGLT2 and DPP4 inhibitors generate glucose-dependent and glucose-independent effects in the targeted organs [14][15][16][17][18][19]. In our study, autophagy was reactivated by both empagliflozin and linagliptin, while glucose levels were reduced, but not to the normal range, only under empagliflozin administration.…”
Section: Reactivation Of Autophagy: a Missing Link In The Mechanism Omentioning
confidence: 44%
“…SGLT2 inhibitors have been shown to enhance sodium excretion and suppress glomerulosclerosis and interstitial fibrosis, inflammation and oxidative stress in diabetic kidney [14][15][16]. In addition, DPP4 inhibitors have been showed to reduce glomerular hypertension and hyperfiltration [17][18][19]. Moreover, empagliflozin has been shown to activate autophagy in tubular cells [20,21].…”
mentioning
confidence: 99%
“…Возможно, в торможение развития ХБП внесло вклад снижение систолического АД и массы тела [44]. Известно, что некоторые сахароснижающие препа-раты, в частности, агонисты глюкагоноподобного пеп-тида-1 и ингибиторы дипептидилпептидазы-4, могут оказывать антиальбуминурический эффект за счет пря-мого действия на почки [47,48]. Очевидно, в основе нефропротективного действия эмпаглифлозина также могут лежать внутрипочечные эффекты.…”
Section: сахарный диабет Diabetes Mellitusunclassified